SIDO DC-DC converter IC for AMOLED display - Tho, Hong Yue (Nanyang Technological University, 2023)
Description: AMOLED display screens are gaining popularity in smartphone foldables and smart watches for their low power consumption, high contrast ratio and light weight flexibility. An unique challenge of the display is the need for a positive and negative power supply with excellent load and line regulation derived from a single lithium battery. Due to PCB space constraint, new methods of DC-DC converters are employed to keep the number of external components low, as well as to achieve higher efficiencies. A state-of-the-art Single Inductor Dual Output (SIDO) architecture is defined for this project. Using a single inductor the circuits will integrate both a positive voltage Booster as well as a negative voltage Buck Booster while achieving efficiencies of 94% and above. In this project, the student will need to design the SIDO converter in BCD technology. Design challenges include analog building blocks like error amplifier, comparator, voltage reference, oscillator, LDO, drivers, control logic and power transistors. The project would be suitable for motivated student with a strong inclination towards analog IC design. If time permits, the student could layout the design. Opportunity for continuation of project derivatives, in pursuance towards a MEng or PHD.